2019
DOI: 10.1155/2019/6934507
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Antibiotics and Antibiotic-Resistant Bacteria in Landfill Sites in Kumasi, Ghana

Abstract: The incidence of antimicrobial resistance among microbial communities is a major threat to global health care and security. Landfills, which are reservoirs for many pharmaceuticals, provide a conducive habitat for antimicrobial-resistant microbes and resistant gene transfer and are therefore a major contributor to the phenomenon of antimicrobial resistance. Hence, this study determined the levels of three widely used antibiotics, metronidazole, penicillin, and amoxicillin, and the occurrence of antimicrobial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 34 publications
2
35
0
Order By: Relevance
“…[54] made similar observation. The antibiotic resistance gene which accounts for MRSA's resistance to several classes of antibiotics is found on insertion sites for plasmids and transposons in mecA complex of MRSA [55]. The presence of Multi-drug resistance strains also shows how S. aureus is developing different methods to resist antibiotics effectiveness.…”
Section: Multidrug-resistant Isolates Among Methicillin-resistant S mentioning
confidence: 99%
“…[54] made similar observation. The antibiotic resistance gene which accounts for MRSA's resistance to several classes of antibiotics is found on insertion sites for plasmids and transposons in mecA complex of MRSA [55]. The presence of Multi-drug resistance strains also shows how S. aureus is developing different methods to resist antibiotics effectiveness.…”
Section: Multidrug-resistant Isolates Among Methicillin-resistant S mentioning
confidence: 99%
“…Earlier studies have also shown that Pseudomonas, Bacillus and Enterobacter are important genera isolated from waste dumping grounds; however their frequency varied at different places depending on local conditions. 16,17,18 Figure 1 simplified The presence of bacteria showing resistance to more than one antibiotic in significant numbers poses potential risk to public health and may lead to decrease in efficacy of medical treatment. 10,12 Antibiotic resistant bacteria have been reported from waste dumping ground in various other studies and they have become a global concern.…”
Section: Resultsmentioning
confidence: 99%
“…20 The practice of not sorting municipal solid waste at source leads to indiscriminate disposal of unused/ expired medicines in municipal solid waste and presence of antibiotics and pharmaceutical drugs at such sites creates selective pressure and helps in developing multidrug resistant bacteria due to mutations. 10,17,21,22 The presence of antibiotic resistant bacteria at such sites may be hazardous to the health of municipality workers, animals and residents of nearby areas. The infections caused by drug resistant bacteria are difficult to treat and increase the cost of medical expenditures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of dumpsites for defecation as well as animal sheds can promote the prevalence of antibioticresistant microorganisms. The improper disposal of unused and expired drugs contributes to the development of drug resistant microbial strains within the environment thereby posing more health risks (Borquaye et al, 2019). The presence of pathogenic microorganisms in soil can bring about possible air pollution as dust particles are taken up by air currents into the atmosphere.…”
Section: Introductionmentioning
confidence: 99%